Physiognomy and Structure of Mangrove Populations in The Region Sekotong Bagek Kembar Ecotourism - Kurniawan, Ramdani; Santoso, Didik; Japa, Lalu (Jurnal Biologi Tropis, 2024)
Physiognomy and mangrove population structure are strongly influenced by changes in land use.  In the Bagek Kembar mangrove ecotourism area to support the fulfillment of human needs that cause changes in mangrove population structure. This study was conducted to determine the physiognomy of mangroves and analyze the population structure of mangrove species in the Bagek Kembar Mangrove Ecotourism area, Sekotong. This research is a type of exploratory and descriptive research using a combination of methods and plots, with a total of 3 stations with 11 transects in the data in the Bagek Kembar mangrove ecotourism area. The results of this study showed that 7 mangrove species were recorded which belonged to 4 families. The value of the diversity index and dominance index in the Bagek Kembar mangrove ecotourism area is included in the low category and the dominance index value is included in the high category, namely the Avicennia marina species. The species diversity index for mangrove seedlings is low (0.625) and the species diversity index for trees and saplings is medium (1.130 and 1.028).